Strategies for Cost Saving Through Social Determinants of Health. Issue 4 (July 2019) - Peeler, Andrew W.
Abstract : Executive Summary: Healthcare costs in the United States are the highest in the world and getting higher. To combat these rising costs, social determinants of health need to be addressed. Healthcare organizations can use one or more of three strategies to address these social determinants: (1) collaborating with community-based organizations to help maintain and improve health, (2) working with policymakers to implement public health interventions, and (3) building housing and communities that are focused on health.